Pengaruh Penerapan Financial Leverage, Good Corporate Governance dan Corporate Social Responsibility Terhadap Nilai Perusahaan - Reni Puspitasari; Anggun Anggraini; Citrawati Jatiningrum (eCo-Fin, 2023)
This research was conducted to examine the effect of implementing financial leverage, good corporate governance, and corporate social responsibility on firm value at banking companies listed on the Indonesia Stock Exchange (IDX) for the 2017 – 2021 period. The population in this study totaled 47 companies. The sample was selescted using purposive sampling method and using outlier data to obtain 29 companies with a total of 137 observations. The study used panel data regression analysis techniques. The results of the research hypothesis show that simultaneously financial leverage, good corporate governance, and corporate social responsibility influence firm value, while partially financial leverage and good corporate governance have a negative effect on firm value and corporate social responsibility has a positive effect on firm value in listed banking companies on the Indonesia Stock Exchange for the period 2017 – 2021